Effects of mitochondrial inhibition by chloramphenicol on the mitotic cycle of human cell cultures - Mittwoch, Ursula (1974)
Chloramphenicol, at concentrations of 500 μg/ml, had a marked inhibitory effect on mitoses in human fibroblasts. Metaphase and G2 appeared to be particularly sensitive to the action of the drug. With concentrations of 1000 μg/ml, or with 500 μg/ml after prolonged exposure, the cells did not reach G2 and no mitoses were seen. The drug required several hours to produce its effect. Studies of oxygen uptake showed no immediate reduction in the respiratory activity of cells at concentrations of 500 μg/ml or 1000 μg/ml but cells which had been in contact with 500 μg/ml of drug for 24 hours showed a marked reduction in respiratory activity. Since the primary effect of chloramphenicol is arrest of mitochondrial protein synthesis, it is concluded that continued synthesis of mitochondrial proteins in the maintenance of the respiratory chain are prerequisites for normal cell division in fibroblasts.